Children Education and Empowerment in an Effort to Improve Healthy Habits in Titi Payung - Br Ginting, Dewi Sartika; Fadhillah, Diana Sari Wahyuni Putri; Cahayani, Retno Sekar Dwigita; Dinda Anggana Putri; Panjaitan, Eka Syahrani; Gultom, Helena (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Titi Payung Village is one of the villages in Air Putih District, Batu Bara Regency, North Sumatra Province. Titi Payung has an area of 165 hectares. There are a total of 2,551 people there, divided into 6 hamlets. Some of the health problems that often occur in school-age children are diseases related to children's personal hygiene and the environment like not brushing their teeth properly and correctly, the habit of washing hands with soap, and so on. Diseases that often arise due to lack of personal hygiene are diarrhea, helmintiasis (stomach worms), toothache, etc. (Saputra, 2013). For this reason, there are several activities that should be encouraged to be able increase knowledge and health quality for students, starting from Kindergarten/Taman Kanak-Kanak (TK) students to Elementary School/Sekolah Dasar (SD) students in Titi Payung Village as a form of prevention of diseases from an early age. The Implementation methods used are lectures and demonstrations. The set of activities carried out are the socialization of the importance of handwashing with soap (Cuci Tangan Pakai Sabun- CTPS) and socialization of maintaining dental and oral health. The results of the implementation of the socializations were the improvents of students' knowledge regarding the correct way to wash hands with soap and the correct way to brush the teeth. As conclusions, the Thematic Students' Study Service/ Kuliah Kerja Nyata Tematik (KKNT) of Universitas Sumatra Utara 2022 helped to increase the knowledge of students in Titi Payung Village and inspire to put more efforts to prevent disease from an early age.